Social Change and the Idea of Urbanity between Late Antiquity and Early Middle Ages - Maraković, Nikolina (Array, 2005)
This paper is an attempt of a multidisciplinary approach to town of late antiquity and early middle Ages. Its aim is to observe the town as a social phenomenon in order to specify and analyse social changes which led to its transformation. The emphasis is given to the town as a social space, defined by social dynamic, and the changes in physical space are used as the opportunity for re-constructing the complex social dynamic in the background. It is also an attempt of re- consideration of the terms like “ de-urbanization” , “ ruralization” , “ dissolution/disappearance of urban culture” or “ returning to the proto-urban formations” as well as perceptions of “ continuity” and “ discontinuity” , which are still very popular in recent debates, but often not analyzed in all its aspects: social, spiritual, physical etc.